2020
DOI: 10.1186/s12884-020-2815-4
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes of dichorionic triamniotic triplet pregnancies after in vitro fertilization-embryo transfer: multifoetal pregnancy reduction versus expectant management

Abstract: Background: Trichorionic triplet pregnancy reduction to twin pregnancy is associated with a lower risk of preterm delivery but not with a lower risk of miscarriage. However, data on dichorionic triamniotic (DCTA) triplet pregnancy outcomes are lacking. This study aimed to compare the pregnancy outcomes of DCTA triplets conceived via in vitro fertilization-embryo transfer (IVF-ET) managed expectantly or reduced to a monochorionic (MC) singleton or monochorionic diamniotic (MCDA) twins at 11-13 + 6 gestational w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
3
8
0
Order By: Relevance
“…While some earlier studies reported that FR in DCTA triplets increased the rate of miscarriage, 7,8,19 several recent studies with relatively large sample sizes and a network meta-analysis have found that reduction (to twins or singletons) and conservative treatment are not significantly different in terms of miscarriage risk. 9,10,20 Similarly, our data showed that the risk of miscarriage following FR to twins (7.1%) or singletons (8.6%) was comparable to that in expectantly managed DCTA pregnancies (4.5%). Moreover, we found no significant difference among the expectant management group, FR to DC twin group, and FR to singleton group in the rate of pregnancies with at least one survivor (86.4%, 89.3% and 89.7%, respectively), which generally agrees with the study by Shaw et al 10 Accordingly, our findings that FR to either twin or singleton pregnancies does not substantially increase the miscarriage risk and that FR does not affect the chance of taking at least one survivor home may be reassuring and may assist decisionmaking for parents who are considering the procedures.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…While some earlier studies reported that FR in DCTA triplets increased the rate of miscarriage, 7,8,19 several recent studies with relatively large sample sizes and a network meta-analysis have found that reduction (to twins or singletons) and conservative treatment are not significantly different in terms of miscarriage risk. 9,10,20 Similarly, our data showed that the risk of miscarriage following FR to twins (7.1%) or singletons (8.6%) was comparable to that in expectantly managed DCTA pregnancies (4.5%). Moreover, we found no significant difference among the expectant management group, FR to DC twin group, and FR to singleton group in the rate of pregnancies with at least one survivor (86.4%, 89.3% and 89.7%, respectively), which generally agrees with the study by Shaw et al 10 Accordingly, our findings that FR to either twin or singleton pregnancies does not substantially increase the miscarriage risk and that FR does not affect the chance of taking at least one survivor home may be reassuring and may assist decisionmaking for parents who are considering the procedures.…”
Section: Discussionsupporting
confidence: 68%
“…In terms of FR to singletons or twins, Liu et al 24 and Li et al 29 found that FR to singletons yielded better pregnancy outcomes compared to those with reduction to DCDA twin pregnancies when procedures were performed at 6–8 weeks by aspiration of embryonic parts. Cai et al 9 reported that FR to singletons significantly decreased the risks of perinatal death and prematurity in comparison with reduction to MC twins by KCl between 11 and 13 +6 weeks. Considering the unique placental structure of the MC component, when couples opt for reduction to DCDA twins after 11 weeks, vascular‐occlusive techniques are required to achieve this goal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although MFPR can reduce the premature delivery rate, the miscarriage rate may increase correspondingly. Therefore, no consensus exists on whether MFPR should be performed and the optimal number of fetal reductions in DCTA pregnancies [ 18 ]. Some research has shown that MFPR to singleton in DCTA may improve the pregnancy outcomes and positively alter gestational week, related to infant mortality and disability [ 9 , 18 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also agreed with Morlando et al (2021) who compared embryo reduction to conservative approaches in triplets and they concluded that better maternal and neonatal outcomes were found in women underwent embryo reduction. Moreover, little or no risks were associated with these procedure [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%